CREATING AND MANAGING SQL DATABASES (Spectrum Journal of Innovation, Reforms and Development, 2023)
Currently, SQL (Structured Query Language) is the structured query language. In particular, SQL is a data partitioning language because the database management system also has other language tools. When creating SQL, it was noted that a relational database, close to simple natural language, was designed as a query language, and the article explains its content in more detail.